2012
DOI: 10.1115/1.4006038
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Mixing Length Turbulence Formulation Into the Dynamic Wake Meandering Model

Abstract: The work presented in this paper focuses on improving the description of wake evolution due to turbulent mixing in the dynamic wake meandering (DWM) model. From wake investigations performed with high-fidelity actuator line simulations carried out in ELLIPSYS3D, it is seen that the current DWM description, where the eddy viscosity is assumed to be constant in each cross-section of the wake, is insufficient. Instead, a two-dimensional eddy viscosity formulation is proposed to model the shear layer generated tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 12 publications
2
69
0
Order By: Relevance
“…This process is seen to be approximately 10 D, on the basis of AL simulations. The details and motivation for this turbulence formulation are given by Keck et al …”
Section: Introductionmentioning
confidence: 99%
“…This process is seen to be approximately 10 D, on the basis of AL simulations. The details and motivation for this turbulence formulation are given by Keck et al …”
Section: Introductionmentioning
confidence: 99%
“…The quasi-steady wake deficit model applies the two-dimensional eddy viscosity model. 6 It also includes the strain-rate contribution from the ABL shear in the wake deficit calculation and the wake expansion as a function of downstream transport distance caused by turbulent diffusion and the rotor pressure field. 7 The wake meandering model describes the stochastic downstream wake transport driven by large scale turbulent structures and this wake meandering model applied is based on the model proposed by Larsen et al.…”
Section: Dwm Overviewmentioning
confidence: 99%
“…7 Based on the calibration by Keck et al, the following values were applied in the calculations: f U = 1.10, f R = 0.98, k 1 = 0.587 and k 2 = 0.0178. 6 The filter function used are shown in Fig. 3.…”
Section: A Wake Deficit Sub-model In the Dwm Modelmentioning
confidence: 99%
“…The concept was used by Bai et al to characterize the development of the wake flow behind a fractal tree and was found to be suitable in the description of transverse momentum fluxes [24]. The approach of describing the Reynolds stress using the eddy viscosity is also applied in the context of wind energy application, where it is in part used in the Dynamic Wake Meandering Model (DWD), which is a computationally inexpensive tool to describe wake effects [25]. Herein, the eddy viscosity and mixing length are calculated from data measured in wind tunnel experiments.…”
Section: Introductionmentioning
confidence: 98%